ANALISIS KUALITAS PELAYANAN PENERBITAN SURAT PERINTAH PENCAIRAN DANA PADA BADAN PENGELOLAAN KEUANGAN DAN ASET DAERAH KABUPATEN YAKUHIMO - Agus Jalak (Jurusan Administrasi Publik, Fakultas Ilmu Administrasi, Universitas Brawijaya, 2023)
Analysis of the quality of Service for Issuing a Fund Disbursement Order In Regional Financial And Management Agency Board Of Yahukimo Regency. This study aims to: describe and analyze the quality of service and the inhibiting factors in the issuance of a Fund Disbursement Order at the Regional Financial and Asset Management Agency of Yahukimo Regency. This research uses a quantitative approach with a descriptive statistics type of research. The sample was taken using purposive sampling techniques of 75 respondents from a population of 294 service recipients. Data were collected through observation, interviews and questionnaires. The data analysis technique used is an descriptive statistics. Based on the results of the analysis, it shows: the quality of service for issuing a warrant for disbursement of funds through five dimensions, tangibless, reliability, responsiveness, assurance and emphaty concern gets quality criteria, namely good and not good. In addition, there are three inhibiting factors in the service of a warrant for disbursement of funds, namely: facilities and infrastructure, the culture of the apparatus and the ability of the apparatus. Thus, it is hoped that the Regional Financial And Management Agency Board Of Yahukimo Regency will be obliged to increase the procurement of facilities and infrastructure and can work with training institutions to develop the capabilities of officials who can encourage the improvement of service quality.